Upaya UPAYA PENINGKATAN PENGETAHUAN WANITA USIA SUBUR (WUS) TENTANG METODE KONTRASEPSI INTRAUTERINE DEVICE (IUD): penyuluhan, metode kontrasepsi IUD - Kholia Trisyani; Orika Crisna; Rina Efriana; Sulistia; Yetty Setiawati; Komalasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2023)
The use of contraception is one of the most effective efforts in the Family Planning Program to control fertility or suppress population growth. In its implementation, efforts are made to ensure that all contraceptive methods or devices provided or offered to the public provide optimal benefits. In choosing a method, a woman must weigh various factors, including health factors, potential side effects of a method, consequences of unwanted pregnancy. However, contraception use for women who are younger and older (age at risk) is much lower than women aged 20-39 years (age not at risk). Participants in Family Planning (KB), namely women of childbearing age (WUS) where one of them uses a method/method of contraception for the purpose of preventing pregnancy or better known as an acceptor. The implementation of this community service was carried out in the Pasar Simpang Health Center work area at the Simpang Simpang Regency, Lampung and was attended by 13 female respondents of childbearing age. The method used in health counseling is the lecture, discussion and question and answer method. In this activity pre and post tests were also carried out regarding the respondents' understanding of contraception.